[Ca₂₄Al₂₈O₆₄]⁴⁺(e⁻)₄ electride as a novel support system for iron-based Fischer-Tropsch synthesis - Motala, Muhammad (University of Cape Town, 2019)
Iron-based Fischer-Tropsch (FT) technology is well established in the industrial production of hydrocarbon resources. The use of a stable inorganic electride as a support system, with potential promoter effects which could replace commonly used alkali metals, may have the potential to open a new facet within the research and development of iron-based FT technology. The hydrothermally produced [Ca₂₄Al₂₈O₆₄]⁴⁺(e⁻)₄ electride material as carrier for Ru nanoparticles for the synthesis of ammonia from its elements has been reported in literature as support system and substitute to conventional alkali promotion. This is due to highly localized electrons present in the crystallographic cages of the material that may serve as a Lewis base and facilitate bond breaking of feedstock molecules adsorbed to the catalytic active sites. The hydrothermal preparation of this electride previously resulted in a surface area of up to 50m²·g⁻¹ and a two-fold rate increase in ammonia production. The low work function of [Ca₂₄Al₂₈O₆₄]⁴⁺(e⁻)₄ is comparable to that of potassium, therefore the iron loading onto the electride is postulated to mimic the promoting effects of potassium(oxide) in the FT synthesis. Following the hydrothermal synthesis of the electride produced at varying evacuation temperatures (800 °C and 1000 °C), supported iron catalysts were prepared using a stoichiometric amount of Fe(acac)₃ precursor to decompose as iron oxide onto the novel support. Iron supported on the unreduced mayenite precursor, [Ca₂₄Al₂₈O₆₄]⁴⁺(O²⁻)₂, and unpromoted precipitated iron diluted in γ-alumina were used as control/baseline catalysts. The testing of these catalysts was conducted at 240 °C and 15 bar with a 2:1 H₂/CO ratio. The electride and mayenite catalysts performed similarly with regards to hydrocarbon selectivities with the precipitated iron bulk catalyst. However, significantly larger CO₂ selectivity and olefin/paraffin ratios were observed for the supported catalysts showing little difference between the electride and its unreduced counterpart.